2014
DOI: 10.1159/000362691
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Impedance and Response to Salbutamol in Healthy Individuals and Patients with COPD

Abstract: Background: Recent studies suggested that the bronchodilator response depends on airway obstruction. The forced oscillation technique (FOT) may help improve our understanding of the changes in respiratory mechanics that occur after the application of a bronchodilator. Objectives: We aimed to (1) assess the response to salbutamol and to compare the impedance changes in healthy individuals and COPD patients, (2) investigate the effects of airway obstruction on this response and (3) evaluate the utility of the FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
5
22
0
Order By: Relevance
“…This is almost in accordance with the findings of da Costa et al15 regarding bronchodilator response using FOT, since we had more patients with milder disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is almost in accordance with the findings of da Costa et al15 regarding bronchodilator response using FOT, since we had more patients with milder disease.…”
Section: Discussionsupporting
confidence: 93%
“…The response of parameters of forced oscillometry (FOT) after salbutamol has recently been described in different GOLD stages. These data showed a significant response in milder stage of COPD compared to controls with a tendency of lower response in more advanced stage 15. However, the bronchodilator response of parameters measured by the closely related IOS method and volume parameters measured by body plethysmography in correlation to other parameters has not been investigated in relation to COPD disease severity based on FEV 1 %p.…”
Section: Introductionmentioning
confidence: 91%
“…Although several authors reported the usefulness of FOT parameters in evaluating COPD [10,19], it is not widely used for this purpose. This is probably due to its high cost, low repeatability [20], and high variances caused by the upper airway structure [21].…”
Section: Discussionmentioning
confidence: 99%
“…advanced lung function bronchodilation in COPD findings of da Costa et al 15 regarding bronchodilator response using FOT, since we had more patients with milder disease.…”
mentioning
confidence: 91%
“…These data showed a significant response in milder stage of COPD compared to controls with a tendency of lower response in more advanced stage. 15 However, the bronchodilator response of parameters measured by the closely related IOS method and volume parameters measured by body plethysmography in correlation to other parameters has not been investigated in relation to COPD disease severity based on FEV 1 %p.…”
Section: Introductionmentioning
confidence: 99%